Correction by "Quertin" of the oxidative-antioxidant system of rats at xenobiotics exposure - Bezrodnaya, A. (The Journal of V.N.Karazin Kharkiv National University. Series «Biology», 2019)
The objective of this study is to determine the possibility of correcting pathological disorders of the oxidative-antioxidant system in the rat organism under the influence of xenobiotics using the flavonoid quercetin, which has an antioxidant, anti-inflammatory, antibacterial, antiviral and immunomodulating effect. Baseline studies have established that when exposed to xenobiotics at a dose of 1/10 and 1/100 DL50, the content of lipid peroxidation products in the serum of rats increases, including 8-isoprostane, TBA-active products (TBA-AP) and diene conjugates (DK). As a result, the state of the antioxidant system also undergoes changes, evidenced by a decrease in catalase activity under the action of xenobiotics in doses of 1/10 and 1/100 DL50, as well as fluctuations in superoxide dismutase content, namely: a decrease under the influence of xenobiotics in a dose of 1/10 DL50 and increase with the action of substances in a dose of 1/100 DL50. After correction with the flavonoid quercetin, a decrease in the content of both primary and secondary POL products in the rat organism, as well as indicators of the state of the oxidative-antioxidant system was established. At the same time, an important for clinical practice relationship was established between the degree of correction of pathological changes in the state of the oxidative-antioxidant system and the dose of toxic effects of xenobiotics. After intragastric administration of “Quertin” in a dose of 25 mg/kg of body weight to rats exposed to polyethylene glycol 400 at a dose of 1/10 DL50, a decrease in serum levels of 8-isoprostan was determined by 14.5%, TBA-AP – by 17.3%, DK – by 15.5%. After exposure to polyethylene glycol 400 at a dose of 1/100 DL50, the content of 8-isoprostane decreased by 12.4%, TBА-AP by 16.8%, and DK by 11.8%. After exposure to polypropylene glycol in doses of 1/10 and 1/100 DL50, the content of 8-isoprostane decreased by 17.7% and 12.5%, TBA-AP – 11.7% and 9.8%, DK – 16.3% and 12.7% respectively. After exposure to ethylene glycol in doses of 1/10 and 1/100 DL50, the content of 8-isoprostane decreased by 22.1% and 14.9%, TBA-AP – 17.3% and 15.2%, DK – 17.6% and 12.2% respectively. Catalase activity increased after the correction by “Quertin” at exposure to polyethylene glycol 400 at doses 1/10 and 1/100 DL50, respectively, by 25.8% and 20.6%; polypropylene glycol – by 26.5% and 23.4%; ethylene glycol – by 19.4% and 15.6%. Superoxide dismutase activity in the blood of rats after the correction of “Quertin” increased at xenobiotic toxification at a dose of 1/10 DL50 (polyethylene glycol 400 – by 29.3%, polypropylene glycol – by 33.5%; ethylene glycol – by 23.2%) and decreased at toxification with xenobiotics at a dose of 1/100 DL50 (polyethylene glycol 400 – by 21.6%, polypropylene glycol – by 26.7%; ethylene glycol – by 18.6%).